Inclusion and Well-Being Among National and Immigrant University Students in Portugal: Avenues for Participatory Research - Maria Odília Teixeira; Márcia Laranjeira (Societies)
In the context of European migratory flows, the inclusion paradigm gives education the responsibility of welcoming, integrating, and training students in an environment that defends humanistic values of equity, respect and dignity. In higher education, this requires institutions to implement inclusive educational policies, promote supportive cultures, and adopt practices that promote change, development, and individual and social well-being. This study examines inclusion variables and their relationship with well-being in a sample of 256 higher education students, including immigrant (n = 107) and non-immigrant (n = 149) students. Immigrant students reported lower perceptions of inclusion across policies (p < 0.001), practices (p < 0.05), and cultures (p < 0.001) compared to their non-immigrant peers. Furthermore, structural equation modeling analysis revealed that inclusive practices of teachers and institutions are significantly associated with the well-being of all students (β = 0.33, p = 0.032). These results highlight the need to implement inclusive educational strategies in both intervention and research. In this context, innovative approaches to participatory research stand out. These approaches must consider the diversity of students, create conditions that promote the well-being of the entire school community, and promote an academic environment that is agentive, relational, and empathetic, and which supports the integration of immigrant students.